Estudio de factibilidad para la creación de una empresa de soluciones integrales para moteras en la ciudad de Pereira (2013)
Biker is a business idea that is characterized by providing comprehensive solutions to the woman rider in the city of Pereira, using the tools of management analysis is performed a feasibility study for the creation of bikers in the city of Pereira, throwing it political and economic conditions are appropriate, through market research was analyzed that there is an acceptance by women riders for a site where they can find everything about your bike specialized in them. If the idea biker follows the guidelines are reflected in research from the organization is viable over time, the support staff can expand within the financial study if made an initial investment of $ 42.2 million of which is done one equity investment of $ 7.2 million and bank financing is done by $ 35 million pesos discussed the loan was made in five years, the balance point of bikers is projected to two years, the IRR (IRR) of the project is 40% considering that the TIO (Internal Rate of opportunity) is 15% and finally NPV (net present value) of the project is $ 5,805,084. Analyzing this information it can be concluded that the project is feasible given that within the different studies prove it.